2019
DOI: 10.1016/j.mayocp.2018.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise and Pharmacological Interventions on Visceral Adiposity: A Systematic Review and Meta-analysis of Long-term Randomized Controlled Trials

Abstract: Objective: To investigate the effectiveness of exercise and pharmacotherapy interventions in reducing visceral adipose tissue (VAT). Patients and Methods:A systematic search of OVID, MEDLINE, SCOPUS, Web of Science, Cochrane Library, ClinicalTrials.gov, New York Academy of Science Grey Literature Report, and Open Grey was combined with hand searches of existing literature. 2,515 titles and abstracts were reviewed. Only randomized controlled trials (RCTs) evaluating the efficacy of monitored exercise or pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 59 publications
1
29
0
1
Order By: Relevance
“…Having shown the feasibility of exercise prescription in the ED, and with some evidence that it could be effective in changing behavior, we call upon emergency physicians and other staff to consider incorporating this approach to combating sedentary lifestyles when addressing health promotion and risk reduction. Although many of the interventions and medications we prescribe on a daily basis have some benefit, few are likely to impact long-term health outcomes as much as effective behavioral change towards increased physical activity [9,10]. As a successful treatment for chronic disease, an effective intervention for reducing obesity, and as a harm reduction tool reducing the risk of death associated with long periods of time sitting, exercise is one of the more cost-effective interventions available for prescription to patients in the ED and other settings [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Having shown the feasibility of exercise prescription in the ED, and with some evidence that it could be effective in changing behavior, we call upon emergency physicians and other staff to consider incorporating this approach to combating sedentary lifestyles when addressing health promotion and risk reduction. Although many of the interventions and medications we prescribe on a daily basis have some benefit, few are likely to impact long-term health outcomes as much as effective behavioral change towards increased physical activity [9,10]. As a successful treatment for chronic disease, an effective intervention for reducing obesity, and as a harm reduction tool reducing the risk of death associated with long periods of time sitting, exercise is one of the more cost-effective interventions available for prescription to patients in the ED and other settings [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis concluded that physical exercise might be more effective than pharmacological interventions (at least when expressed relative to the magnitude of body weight loss) for reducing VAT. 48 Both drugs (glucagon-like peptide-1 and receptor agonists, or long acting insulin analogue, recombinant hormone) 20,49,50 and bariatric surgery 51 have been reported to produce large reductions ($36% 49 and 27%, 51 Excess levels of EAT are associated with an increased release of pro-inflammatory adipokines, 17 which can promote the development of atherosclerosis and other cardiovascular complications. 18,19 In turn, endurance exercise is not only associated with a reduced EAT-as confirmed in the present meta-analysis-but also with a reduced concentration of adipokines that can be released from EAT such as resistin.…”
Section: F I G U R Ementioning
confidence: 99%
“…Unfortunately, Rao et al 7 were not able to assess the effect of exercise on other cardiometabolic risk factors or mental health outcomes because of the lack of information on the included studies; such relevant information enables a fuller understanding of the benefits of exercise on health. Of note, although exercise seems to selectively reduce VAT, even in the absence of overall body weight loss, the beneficial effects of exercise extend to multiple organs and systems.…”
mentioning
confidence: 99%